Catalytic performance of gallium oxide based-catalysts for the propane dehydrogenation reaction: effects of support and loading amount. Issue 8 (17th January 2017) - Shao, Chun-Tao; Lang, Wan-Zhong; Yan, Xi; Guo, Ya-Jun
Abstract : Ga2 O3 -based catalysts supported on different supports (ZSM-5, SBA-15, γ-Al2 O3 and SiO2 ) were prepared, and the effects of supports and Ga2 O3 content (1–9 wt%) on their catalytic performance for the propane dehydrogenation reaction were discussed. Abstract : The different materials (ZSM-5, SBA-15, γ-Al2 O3 and SiO2 ) were used as supports for Ga2 O3 -based catalysts for the propane dehydrogenation reaction, and the effect of Ga2 O3 content (1–9 wt%) for x Ga2 O3 /SBA-15 catalysts on the catalytic activity was discussed. It is found that the supports determine the porous features, the state and dispersion of Ga species, and the acid–base properties of the corresponding catalysts. The existence of strong acid sites in catalyst can lead to more well-dispersed Ga species. The satisfied catalytic performances are obtained over 5Ga2 O3 /ZSM-5 and 5Ga2 O3 /SBA-15 catalysts. Among the Ga2 O3 -based catalysts with different supports, the 5Ga2 O3 /ZSM-5 sample exhibits the highest catalytic activity, which possesses the maximum well-dispersed gallium species and high dehydrogenation efficiency gallium ions (Ga δ + cations, δ < 2), and the 5Ga2 O3 /SBA-15 catalyst exhibits the highest catalytic stability. Furthermore, as for the x Ga2 O3 /SBA-15 samples, the 5Ga2 O3 /SBA-15 sample exhibits the best catalytic performance. The initial propane conversion and propylene selectivity are above 32.0% and 90.0% respectively, and a final propane conversion of 17.0% is obtained after 30 h reaction. With the increase of Ga loading, the Ga species are easily agglomerated and destroy the structural integrity of the SBA-15 support, which is unfavorable to the propane dehydrogenation reaction.